2014
DOI: 10.4236/pp.2014.513130
|View full text |Cite
|
Sign up to set email alerts
|

A Structure and Antioxidant Activity Study of Paracetamol and Salicylic Acid

Abstract: The paracetamol has more antioxidant properties than the salicylic acid on the several oxidative stress-forced models and one possible mechanism is due to electron or hydrogen transfer by the evaluated hydroxyl radicals. The antioxidant mechanism for the compounds studied here was performed by molecular modeling using quantum chemical calculations at the B3LYP level of theory. Our results show that the paracetamol has more antioxidant properties than the salicylic acid in experimental and theoretical studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This antagonism could be by preventing Ca 2+ loading in to the erythrocyte and/or inhibiting calcium-induced K + loss from the cell 6 . Since there are no reports in the literature suggesting that paracetamol could inhibit Ca 2+ influx in the human erythrocyte, and since the present study showed that paracetamol doesn't prevent plasma recalcification (clotting) indicating no Ca 2+ binding to the drug, it seems that this antagonism could be due to the antioxidant activity of paracetamol that has been reported in human erythrocytes 16,17,18,19 , and also shown in the present study (Table 1), with consequent anti-lipidperoxidation activity that has been reported previously 16,18 , and also shown in the present study (Fig. 4).…”
Section: Discussionmentioning
confidence: 63%
“…This antagonism could be by preventing Ca 2+ loading in to the erythrocyte and/or inhibiting calcium-induced K + loss from the cell 6 . Since there are no reports in the literature suggesting that paracetamol could inhibit Ca 2+ influx in the human erythrocyte, and since the present study showed that paracetamol doesn't prevent plasma recalcification (clotting) indicating no Ca 2+ binding to the drug, it seems that this antagonism could be due to the antioxidant activity of paracetamol that has been reported in human erythrocytes 16,17,18,19 , and also shown in the present study (Table 1), with consequent anti-lipidperoxidation activity that has been reported previously 16,18 , and also shown in the present study (Fig. 4).…”
Section: Discussionmentioning
confidence: 63%
“…In fact, previous works for the antioxidant activity of these drugs have focused mainly on the general capacity of the paracetamol to decrease the malondialdehyde formation in the lipid peroxidation systems (Orhan and Sahin, 2001;Maharaj et al, 2004), whereas the salicylate working as scavenger of hydroxyl radical is very well known (Dinis et al, 1994;Sairam et al, 2003;Maharaj et al, 2006;Borges et al, 2014). Soon, hydroxyl radical can be formed via Fenton and Haber-Weiss reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous experimental works have been done on APAP to understand the structure, structural assignment and stability [11][12][13] , the mechanism of action [14][15] , photocatalytic degradation [16][17] , method validation for quantitative determination [18][19][20] , to improve analgesic and antipyretic activities and to reduce side effect 21 and applications in prevention of metal corrosion from acid rain 22 . Compared to experimental works, there is no so many computational research yet on APAP.…”
Section: Introductionmentioning
confidence: 99%